Pengaruh Couple Prenatal Class Terhadap Kecemasan Ibu Dalam Menghadapi Persalinan Di Klinik Hana Jogonalan Klaten - Anik Kurniawati; Endang Suwanti (Jurnal Kebidanan dan Kesehatan Tradisional, 2019)
The husband is a wife's assistant and often as a decision maker both during pregnancy and childbirth, therefore the husband also needs to get the same information as pregnant women. According to Lutfiatus Sholihah (2004), during pregnancy, the husband must also be invited to prepare to welcome the arrival of the child, because not all husbands are ready to mentally wait for his wife who is in pain, sometimes they even panic and can not calm the wife who was giving birth.Based on a preliminary study conducted that the class of pregnant women is only given to mothers without involving the husband or partner. Preliminary study data also shows that there are still many pregnant women who come to health workers during the fake labor phase. Pregnant women arrive early due to anxiety and fear of facing labor.The purpose of this study was to determine the effect of prenatal class couples on maternal anxiety in facing labor at the Hana Jogonalan Klaten clinic. This type of research is Quasi experiment, with post test design without control group design. The study was conducted at the Klaten Jogna Hanna clinic from May to August 2018.The target population in this study were pregnant women with a minimum gestational age of 36 weeks with a total population of 20 respondents The sampling technique in this study was total sampling. 10 respondents were given classes of pregnant women with husband's assistance and 10 respondents were given classes of ordinary pregnant women, classes of pregnant women were given 2 times in 1 month.The respondent's anxiety state was measured using the Hamilton Rating Scale For Anxiety (HRSA) research instrument. Data analysis was performed by univariate and bivariate analysis using the Spearman Rank test. The results showed there was no effect of couple prenatal class on maternal anxiety with a p value of 0.193 and a correlation coefficient of 0.302.